Concrete slab waterproofing application - Faizal Hanizam, Farah Nabila (Universiti Teknologi MARA, Perak, 2021)
In construction, waterproofing increases the performance of several different surfaces. In addition, in order to ensure the comfort of the house or office to be used after the building is done, waterproofing materials should be added. The application of waterproofing and the defects of waterproofing in construction will therefore be addressed in this report. This study was conducted at the Pangsapuri Blok 1 Hingga Blok 5, Seksyen 19, Shah Alam for the building envelope. The objective of this report is to clarify the application of waterproofing used for the concrete slab in a construction site, to describe the benefit of the types of waterproofing used in construction, and to identify the causes of a defect of waterproofing.